Changes in the phytoplankton‐bacteria coupling triggered by joint action of UVR, nutrients, and warming in Mediterranean high‐mountain lakes. (14th December 2015) - Durán, Cristina; Medina‐Sánchez, Juan Manuel; Herrera, Guillermo; Carrillo, Presentación
Abstract: From an extensive study, we determined that heterotrophic bacterial production (HBP) variance in Sierra Nevada (Spain) lakes was explained mainly by excretion of organic carbon by algae (EOC), underlining a bacterial dependence on algal carbon. Subsequently, we studied how the interaction among global change factors such as ultraviolet radiation (UVR), nutrient inputs, and increased temperature affected this phytoplankton‐bacteria coupling through in situ factorial experiments in two model high‐mountain lakes, La Caldera, and Las Yeguas. Bacterioplankton were more sensitive than phytoplankton because the joint action of increased temperature and nutrient‐addition unmasked an inhibitory UVR effect on HBP while reducing the inhibitory UVR effect on primary production (PP) (in La Caldera) or augmenting the net PP values (in Las Yeguas). The interaction among the three factors had a different effect on phytoplankton‐bacteria coupling depending on the lake. Thus, in the colder lake (La Caldera), EOC was not adequate to meet the bacterial carbon demand (BCD), leading to a mismatch in phytoplankton‐bacteria coupling. Contrarily, in the warmer lake (Las Yeguas), the phytoplankton‐bacteria coupling was accentuated by the interaction among the three factors, with EOC exceeding BCD. These contrasting responses of phytoplankton‐bacteria coupling may affect the microbial loop development, becoming reinforced in warmer and less UVR‐transparent high‐mountain lakes, but weakened in colder and more UVR‐transparent high‐mountain lakes, with implications in the C‐flux of these sentinel ecosystems in a scenario of global change.